AN EPIDEMIC OF ECHOVIRUS TYPE 30 MENINGITIS IN AN ARCTIC COMMUNITY - GRAVELLE, CLIFTON R.; NOBLE, GARY R.; FELTZ, ELMER T.; SASLOW, ARNOLD R.; CLARK, PAUL S.; CHIN, TOM D. Y. (Oxford University Press, 1974)
In June of 1969, an epidemic of aseptic meningitis occurred in Bethel, Alaska. A total of 97 cases were identified; 40 were classified as aseptic meningitis and 57 as minor febrile illness. A random sample survey of 277 persons in a population of 2000 revealed an illness rate of 8.7%. The highest attack rates were in children under 10 years of age. Evidence of infection with echovirus 30 was found by virus isolation or antibody rise in 69 of 78 (88%) ill persons and 83 of 112 (74%) well persons. Echovirus 30 was recovered from 2 of 18 spinal fluids with fewer than 50 leucocytes/cu mm and from 5 of 10 spinal fluids with more than 50 leucocytes. Pleocytosis was found in 11 of 16 persons who were not diagnosed as having aseptic meningitis. Pre-epidemic serum samples had been collected from 143 persons as part of a prospective family study of respiratory disease. Fourfold antibody rises between these and post-epidemic sera were considered evidence of infection in ill and well people; the ratio of clinical to subclinical infection thus calculated was 1: 2.